Pelayanan Guru Bimbingan Dan Konseling Dengan Memanfaatkan Teknologi Informasi - Ayasi Alhajami; Muhammad Andra Nurramadhan; Muhammad Denis Irwinsyah; Ati Kusmawati (Concept: Journal of Social Humanities and Education, 2024)
Information Technology (IT) is the study, design, development and support, especially of software. With increasingly advanced developments, the rapid progress of information technology has presented a new world that allows interaction to take place quickly and instantly, one of which is via the internet. The presence of the internet influences almost all interaction patterns, including interaction patterns between counselors and their clients. The development of this technology provides various conveniences in types of humanitarian services, including the counseling service process. Guidance and counseling services should be directed at how to equip digital generation students with superior characters who utilize information and communication technology, so that they can lead students towards a bright future. The media used in counseling are computers and audio-visual devices. The role of technology can be very useful in supporting the Guidance and Counseling Teacher service process so that it is more effective, efficient, creative, varied and innovative in finding the latest information in the service process. The advantage of using a website in counseling services is that it opens up opportunities for providing counseling services without time limits, because it can be done wherever and whenever needed.